The origins of UNICEF, 1946-1953 - Morris, Jennifer M. (Lexington Books, an imprint of The Rowman & Littlefield Publishing Group, Inc., 2015)
Started as a temporary organization, UNICEF navigated Cold War tensions in order to provide assistance to millions of children and their parents throughout the world. The Origins of UNICEF, 1946-1953 reveals how the most well-known child-relief aid organization in the world came into being.